Etnopharmacology of medicinal plants used by the rural and riverside population of the municipality of Itacoatiara- AM (Research, Society and Development, 2022)
The cultural importance of the traditional knowledge of the Amazonian peoples about medicinal plants has been increasingly valued in the contexto of public health systems and aroused the interest of the pharmaceutical industry in pharmacological, phytochemical and agronomic studies applied to the search for new medicines. In this study, we sought to measure the habits arising from the traditional use of medicinal plants by users of a Basic Health Unit. This was na ethnopharmacological study, carried out by analyzing interviews with rural and riverside population assisted by a Basic Health Unit in the city of Itacoatiara-AM, whose collected data were analyzed and interpreted using descriptive statistics. The variables showed a prevalence of female individuals, aged between 18 and 81 years, high school and family income below the minimum wage. Thirty-six species of medicinal plants were mentioned, with a predominance of the preparation of infusions and indications such as sedative, in epigastric pain and in inflammatory processes. The results contribute to the rescue and appreciation of popular knowledge; to expand and consolidate the safe and effective use of medicinal plants in the context of primary health care and to promote the development and improvement of the quality of life of the population of the municipality of Itacoatiara- AM.